The Learning Achievement of Grade Seven Students on Landscape Painting Through 3D Paper Model - Kheuasida, Sriudon; Bovornkitti, Lertsiri (Fine Arts Journal: Srinakharinwirot University, 2014)
An effective teaching and learning management is to give students the optimum chance to participate and gain learning experience by themselves. A teacher’s role is the facilitator who arranges proper learning activities and materials on surrounding pictures. This research aims to study the learning achievement of Grade 7 students on landscape painting through 3D paper model and the learning method that does not use 3D paper model. The samples in this study are 70 students of Grade 7 in the second semester of the academic year 2013 at Sarasas Witaed Nimitmai School, Klongsamwa, Bangkok. Cluster random sampling is used to select the population samples from 2 classes which have 35 students each. The experimental study is conducted by using 3D paper model for 12 weeks at 60 minutes. The research tools are 3D paper model, pretest and posttest, and questionnaires on satisfaction in using 3D paper model. The researcher conducts the research in compliance with the experiment plan. The method of data analysis is to find the average, standard deviation and t-test for dependent-samples. The research results are that the learning achievement of Grade 7 students learning landscape painting through 3D paper model is improved at 0.01 statistically and significantlyand the satisfaction on learning through 3D paper model is in the highest level.